THE ROLE OF MYOFIBRILS IN THE FORMATION OF GEL OF SURIMI GIANT TREVALLY (Caranx sp) - Kaliky, Nurainy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Giant trevally (Caranx sp) is one type of by-catch fish that is often thrown back into the sea. To increase the economic value of this fish, one of the alternatives is making surimi. This study aims to study the effect of inhibition of softening gel (Modori) of surimi by egg white protein with various concentrations. The method used is an experiment with 2 treatments, namely the addition of egg white protein (A) with a concentration of ; A1 = 1%, A2 = 2% and A3 = 3% and the gelling temperature (B) is 45ºs C for 20 minutes - 85º C for 15 minutes. Completely Randomized Design (CRD) was used to analyze the data with two replications and continued Analysis of diversity (ANOVA). The parameters analyzed in this study include objective parameters, namely water content, protein content and subjective parameters of color, folding test and texture. The results showed that water content, color, texture and folding test increased while protein content decreased.